Development of Community-Based Early Warning System (CBEWS) in enhancing community preparedness for dam-related disasters in Malaysia - Ghazali A.; Thiruchelvam S.; Muda R.S.; Mustapha K.N.; Kadir A.K.; Norkhairi F.F.; Yahya N.; Hakimie H.; Isa A.A.M.; Mamat A.F.; Hasini H.; Sahari K.S.M.; et al. (Akademi Sains Malaysia, 2023)
Series of catastrophic oods that we have witnessed over the last decade in Malaysia have necessitated the adoption of reliable early warning system. Ultimate concern during any event of natural or manmade disaster would be information dissemination to lessen the disaster impact on lives and property. The Bertam Valley incident in the wee hours of 23rd October 2013 has been considered as the game changer of how we view the role of vulnerable communities in facing dam-related disasters. Empowerment of local communities has been considered as vital in disaster management, as they are often the first responders to disaster. Local Community-Based Early Warning System (CBEWS) is a smart mechanism operated by the communities. This study revolves around the actual implementation of such system in Cameron Highlands in the effort of increasing human resilience towards damrelated disasters. While establishing the system, the Bertam Valley community has received support from different individuals and organisations. It is paramount that the community develops and maintains close coordination and strong links with these stakeholders. The performance of early warning systems can be evaluated via key parameters such as timeliness, accuracy, reliability, user friendliness, exibility, and costs & benefits. 2018, Akademi Sains Malaysia.